Myśl ekonomiczna kalwinizmu - Chmielewska, Justyna (Annales. Etyka w Życiu Gospodarczym, 2023)
The aim of the paper is to present the economic thoughts of John Calvin and his followers, referring to current issues, such as money lending, usury, or work. The latter, according to the famous thesis of Max Weber, received spiritual value by acting as a bridge between God's will and daily life. The hypothesis of this article differs somewhat from this conviction, assuming that the main economic elements of Calvinist thought have been the consequence of the release of temporal realities from the influence of the direct action of God, according to the protestant theology of the radical separation of nature and grace. Initiated by Protestantism, the dichotomy of nature and grace seems to have important consequences for economic thought. The salvific dimension of human fate remained in the hands of God, he depends entirely on its favour in connection with the dogma of predestination. In the earthly life, a human being was treated as a part of nature, his survival depended on skill and determination. in the struggle with nature, devoid of the grace of God, ruled by the law of necessity. Survival and a better life depended primarily on human labour and effort. The flourishing of economic life has resulted not only from the ethical role of work, but also from the fact that it was no longer inhibited by religious restrictions. Thus, modern man was born, more and more aware of his subjectivity, subordinating nature to himself building the human world in place of the natural world. Building a modern society and economy is part of the Protestant ethos of mastering nature.